HUBUNGAN DEWAN DIREKSI, KEBERAGAMAN GENDER DAN KINERJA BERKELANJUTAN TERHADAP PENGHINDARAN PAJAK - Tanujaya, Kennardi; Anggreany, Elva (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of the size of the board of directors on taxavoidance and also to expand the existing literature by examining the mediatingeffect of sustainability performance on the relationship between gender and taxavoidance in the Indonesian context. This study will examine all companies listed onthe Indonesia Stock Exchange that meet the criteria other than the financial sectorfrom 2016-2020. Tax avoidance which is the dependent variable is measured byCETR (Cash Effective Tax Rate) using partial least squares (PLS) software. Thesample used was 148 companies using a purposive sampling procedure. The resultsof this study indicate that the size of the board of directors has no significant effecton tax avoidance, gender diversity has a significant negative effect on tax avoidance,but with the inclusion of sustainability performance as a mediating variable in therelationship between gender diversity and tax avoidance, the results are notsignificant